A fotografia na mediação da arte - Alves, Ignez Capovilla (2019)
While museums establish a status of conservation and valorization of works, they also decontextualize the arts from their place of origin, proposing recontextualizations, rereading and interpretations to the public who frequent these spaces. It is a historical approach to photography and the problematizations arising from its technical transformations. To understand this context, one observes the impact of the concept of reproducibility on Walter Benjamin and its implications on the idea of distortion, defended by John Berger. These discussions also reach the ideas of image equalization, proposed in the works of André Malraux and Aby Warburg. In this sense, we highlight the contribution of artists whose photographic works restore to the viewer a broader meaning of the work of art and propose different possibilities to review the history of art, to question the system of arts, as well as the form of organization of museums and photographic appropriation, such as Bruno Moreschi (Brazil) and Louise Lawler (USA).